2010
DOI: 10.1007/s00417-010-1452-4
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis and review on the effect of bevacizumab in diabetic macular edema

Abstract: Current data suggests that IVB is an effective short-term treatment for diabetic macular edema, and that its efficacy wanes after 6 weeks. More trials exploring the therapeutic role of intravitreal bevacizumab in DME need to be conducted to define the role of bevacizumab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
7

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 51 publications
2
30
1
7
Order By: Relevance
“…In ophthalmology, bevacizumab has emerged as a therapeutic agent for retinal vascular diseases 51 and has been used as an off -label agent in a number of ocular diseases, including DR and DME 52 . Th ere have been a number of published trials with short follow up and using different treatment doses/regimens and diff erent comparison groups that investigated the eff ect of bevacizumab in DME 53 . Th e BOLT study compared intravitreal bevacizumab to focal laser and found superior VA results at 12 months (+8 vs. -0.5 letters), 5.1 times greater odds of gaining >10 letters, and a decrease in CRT (130 μm vs. 68 μm) in bevacizumab versus laser group 54 .…”
Section: Novel Treatment Options For Dmementioning
confidence: 99%
“…In ophthalmology, bevacizumab has emerged as a therapeutic agent for retinal vascular diseases 51 and has been used as an off -label agent in a number of ocular diseases, including DR and DME 52 . Th ere have been a number of published trials with short follow up and using different treatment doses/regimens and diff erent comparison groups that investigated the eff ect of bevacizumab in DME 53 . Th e BOLT study compared intravitreal bevacizumab to focal laser and found superior VA results at 12 months (+8 vs. -0.5 letters), 5.1 times greater odds of gaining >10 letters, and a decrease in CRT (130 μm vs. 68 μm) in bevacizumab versus laser group 54 .…”
Section: Novel Treatment Options For Dmementioning
confidence: 99%
“…In contrast, a high false-negative rate puts patients at risk of vision loss even when effective treatment is readily available. [31][32][33] An increased number of patients with vision loss as a consequence of false-negative screening will, in turn, translate into a financial burden on the health care system and society. In view of the rising prevalence of diabetes and its complications worldwide, 34 a more reliable and costeffective screening strategy is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, our suggestion, which is based solely on a similar number of cataract operations in the three groups, put some biases on the cataractogenic effect of the drugs studied. We were not able to document changes in the foveal avascular zone during the follow-up in each case [13,14]. This study has limitations in the evaluation of macular function in this respect.…”
Section: Discussionmentioning
confidence: 99%
“…This study, which was performed on DDME patients without prior macular photocoagulation, yields similar evidence (not shown). Current reviews including meta-analysis for treatments of IVB and IVTA in DDME seem to be inconclusive; however, they conclude with cautious optimism [12,13]. These studies indicate that the effect(s) of intravitreal injection(s) are more or less temporary, and IVTA has an inherent risk of complications, i.e.…”
Section: Discussionmentioning
confidence: 99%